Factors associated with body weight status among Malaysian adolescents living in day-school hostels - Lai, Soke Ching (2016)
The lives of adolescents in school hostels are well-managed with respect to their daily food intake and physical activity. They are likely to be physically active and are assumed to consume nutritious food. However, little is known about their body weight status and its associated factors. Thus, this study determined the association between sociodemographic characteristics, dietary practice, physical activity, knowledge, attitude and practice on healthy lifestyle, Transtheoretical Model of behavioral change on healthy diet and exercise, and body image perception with body weight status among Malaysian adolescents living in day-school hostels. A total of 4189 school-going adolescents (aged 13 years) were involved in this study. Information on socio-demographic characteristics, dietary practice, physical activity, knowledge, attitude and practice on healthy lifestyle, Transtheoretical Model of behavioral change on healthy diet and exercise and body image were collected using a self-administered questionnaire. Body weight and height were measured while BMI-forage (z-score) was determined using WHO Growth Reference. One day 24-hour dietary and physical activity recalls were obtained by face-to-face interview. Multivariate general linear regression analysis was conducted. Majority of the respondents were females (59.5%), Malays (70.5%), from rural area (70.2%) and were achieved pubertal status (65.9%). The prevalence of overweight and obesity [Both sexes: 23.3% (95% Confidence Interval [CI]: 22.1, 24.7); Males: 21.7% (95% CI: 19.8, 23.8); Females: 24.5% (95% CI: 22.8, 26.2)] was about six times higher than the prevalence of thinness [Both Sexes: 4.3% (95% CI: 3.7, 5.0); Males: 5.6% (95% CI: 4.5, 6.9); Females: 3.4% (95% CI: 2.7, 4.2)] among the respondents. The mean total daily energy intake was 2070 Kcal (95% CI: 2045, 2097) and the mean total daily energy expenditure was 1965 Kcal (95% CI: 1952, 1978). The mean score for knowledge and attitude were 18.6 (95% CI: 18.4, 18.7) and 98.9 (95% CI: 98.4, 99.2), respectively. Selfefficacy and perceived benefits on healthy diet had mean score of 15.8 (95% CI: 15.7, 15.9) and 27.8 (95% CI: 27.6, 27.9), respectively. Slightly less than half of the respondents (48.9%, 95% CI: 47.4, 50.5) had correct perception on body weight, about one in three respondents (32.4%, 95% CI: 31.0, 33.9) satisfied with their body size and two in three respondents (68.2%, 95% CI: 66.7, 69.6) had correct perception on healthy body size. Bivariate analysis indicated that sex, area, pubertal status, energy expenditure per kilogram body weight, knowledge and attitude on healthy lifestyle, self-efficacy and perceived benefits on exercise, body weight status perception, body size satisfaction and healthy body size perception were significantly associated with BMI-for-age of the respondents. No associations were found between ethnicity, dietary practice, physical activity level, practice on healthy lifestyle, stages of healthy diet behavioral change, stages of exercise behavioral change, self-efficacy on exercise, perceived barriers for both healthy diet and exercise, and perceived benefits for exercise with BMI-for-age of the respondents. In multivariate general linear regression model, being female (β= 0.620) having achieved pubertal status (β= 0.408), positive attitude on healthy diet (β= 0.005), better self-efficacy on healthy diet (β= -0.014), lower energy expenditure per kilogram body weight (β= -0.075), incorrect body weight status perception (β= 0.177), dissatisfaction with body size (β= 0.144), and incorrect healthy body size perception (β= 0.113) significantly contributed to the high BMI-for-age of the respondents at p<0.05 level of significance explaining 34.7% of the variance in BMI-for-age (R2=0.347, F=119.512, p<0.001). Dual-form of malnutrition co-exists with overweight and obesity were more prevalent than thinness. Future healthy body weight intervention programes should emphasize on sex-specific, attitude on healthy lifestyle, self-efficacy on healthy diet and body image approach among these adolescents living in day-school hostels.